Manufacturability, Mechanical Properties, Mass-Transport Properties and Biocompatibility of Triply Periodic Minimal Surface (TPMS) Porous Scaffolds Fabricated by Selective Laser Melting. (October 2020) - Ma, Shuai; Tang, Qian; Han, Xiaoxiao; Feng, Qixiang; Song, Jun; Setchi, Rossitza; Liu, Ying; Liu, Yang; Goulas, Athanasios; Engstrøm, Daniel S.; Tse, Yau Yau; Zhen, Ni
Abstract: Selective laser melting is a promising additive manufacturing technology for manufacturing porous metallic bone scaffolds. Bone repair requires scaffolds that meet various mechanical and biological requirements. This paper addresses this challenge by comprehensively studying the performance of porous scaffolds. The main novelty is exploring scaffolds with different porosities, verifying various aspects of their performance and revealing the effect of their permeability on cell growth. This study evaluates the manufacturability, mechanical behaviour, permeability and biocompatibility of gyroid scaffolds. In simulations, mechanical behaviour and permeability exhibited up to 56% and 73% accuracy, respectively, compared to the experimental data. The compression and permeability experiments showed that the elastic modulus and the permeability of the scaffolds were both in the range of human bones. The morphological experiment showed that manufacturing accuracy increased with greater designed porosity, while the in vitro experiments revealed that permeability played the main role in cell proliferation. The significance of this work is improving the understanding of the effect of design parameters on the mechanical properties, permeability and cell growth of the scaffolds, which will enable the design of porous bone scaffolds with better bone-repair effects. Graphical abstract: Unlabelled Image Highlights: Proposing a design method to improve the accuracy of manufactured porosity of high-porosity scaffolds. Comprehensively studying the manufacturability, mechanical and mass transport properties, and biocompatibility of gyroid scaffolds. The simulation of the mechanical and mass-transport properties of scaffolds both showed predictability. Greater pore size gave bone scaffolds higher permeability, which promotes bone repair The factors possibly affecting the prediction accuracy of the mechanical and mass-transport properties of lattice scaffolds were summarised.